3(x-3)+5=-2(x+3)+5x

Simple and best practice solution for 3(x-3)+5=-2(x+3)+5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-3)+5=-2(x+3)+5x equation:


Simplifying
3(x + -3) + 5 = -2(x + 3) + 5x

Reorder the terms:
3(-3 + x) + 5 = -2(x + 3) + 5x
(-3 * 3 + x * 3) + 5 = -2(x + 3) + 5x
(-9 + 3x) + 5 = -2(x + 3) + 5x

Reorder the terms:
-9 + 5 + 3x = -2(x + 3) + 5x

Combine like terms: -9 + 5 = -4
-4 + 3x = -2(x + 3) + 5x

Reorder the terms:
-4 + 3x = -2(3 + x) + 5x
-4 + 3x = (3 * -2 + x * -2) + 5x
-4 + 3x = (-6 + -2x) + 5x

Combine like terms: -2x + 5x = 3x
-4 + 3x = -6 + 3x

Add '-3x' to each side of the equation.
-4 + 3x + -3x = -6 + 3x + -3x

Combine like terms: 3x + -3x = 0
-4 + 0 = -6 + 3x + -3x
-4 = -6 + 3x + -3x

Combine like terms: 3x + -3x = 0
-4 = -6 + 0
-4 = -6

Solving
-4 = -6

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| X-0.20=36 | | 5y^2-2x+2=0 | | x*2+6*3=12*3*x | | 18t+13=15t | | 2z=a-bj | | xy=1*3 | | 2.8x+5.6=8.4 | | f(4)=-2x-1 | | x*3x=486 | | (2x+7)(x+5)=0 | | 2x+7y-21=0 | | 2.8+5.6=8.4 | | x-2/4=5/7 | | 7a-4=2a+20 | | http://x-2/4=5/7 | | -4x-14=x+1 | | .25+91=180 | | (4x-9)-(11x+6)=0 | | 35n^2-8n-16=0 | | (2x+3)2-(2x-3)(2x+3)=2(3x-5) | | 35n^2-8n=0 | | 3x+4=-3(4x-8) | | (3x-7)(5x+2)=10 | | 5j+z=3 | | 1/16x-.31 | | 2x=2*24 | | -2+k/4=-4 | | 3y+2x-n=12 | | 5-4a=41 | | 21x+2=14 | | -16X+8X=8X+2 | | 6+30+4x=10 |

Equations solver categories